Leveraged Carry Trade Portfolios - Zsolt Darvas (Hungarian Academy of Sciences, Institute of Economics, 2008)
Studying all possible pairs of eleven major currencies and eleven portfolios in 1976-2008 we show that, when there is no leverage, carry trade is significantly profitable for most currency pairs and portfolios. Positive returns do not diminish in time providing a strong case against the hypothesis of uncovered interest rate parity. We explain these findings with the leveraged nature of carry trade: leverage may increase profitability but it materially increases downside risk. We argue that market inefficiency is related to the level of leverage.
Keywords: C32; F31; G11; G15; 330; Bootstrap; Currency market; Diversification; Leverage; Uncovered interest rate parity; Devisenmarkt; Währungsspekulation; Devisenmarkt; Zinsparität; Portfolio-Management; Bootstrap-Verfahren; Welt